Professional male prostitution: a neglected phenomenon - Poel, Sari van der (Crime, law and social change, 1992)
Male prostitution is generally regarded as a problematic phenomenon. This paper refutes this view by showing that most researchers have consistently selected only the problematic categories of male prostitution for their studies while ignoring successful prostitutes. A second difficulty is that many researchers explain male prostitution in terms of the individual psychosocial characteristics of those who practice it. Consequently little is known about male prostitution as an occupational/professional career. Based on ethnographic research in the world of male prostitution in Amsterdam, the occupation is analyzed as a commercial service-oriented business with economic and social characteristics typical of other small- and medium-sized businesses.